(untitled) - The World Bank in Vietnam (WB) (Ha Noi, 2004)
The Rural Transport Project for Vietnam will reduce travel costs and improve access to markets, off-farm economic opportunities, and social services for poor rural communities in the 33 participating provinces in Northern and Central Vietnam. The project consist of the following components: (A) This component will finance the rehabilitation and improvement of about 3,100 kms of the core rural roads network (district, commune and village roads) in 33 provinces in Northern and Central Vietnam. (B) This component will provide additional finance to tackle the under funding of maintenance on the district roads network. (C) A comprehensive capacity development framework has been designed to support the institutional strengthening, organizational effectiveness and individual skills development of the rural transport sub-sector. This component has four sub-components: Sub-component C.1: Advisory Services; Sub-component C.2: Independent review consultants; Sub-component C.3: Facilities to support MOT and PDoTs; Sub-component C.4: Training to strengthen individual skills development.
Keywords: Roads,Đuờng giao thông,Transportation,Giao thông vận tải